Performance Comparison Between Diesel Fuel And Biodiesel Using A Low Cost Single Cylinder Diesel Engine Dynamometer - Mohd Zaini, Jamaludin; Safarudin Gazali , Herawan; Yusmady , Mohamed Arifin; Fauzi, Ahmad (Trans Tech Publications, 2014)
Nowadays, biodiesel from non-edible feedstock is gaining more concern than edible oil to substitute diesel fuel. The purpose of this study is to investigate the performance of low cost single cylinder diesel engine fuelled by regular diesel and B5 biodiesel of castor and jatropha. The experiments were conducted to identify the performance of a low cost single cylinder diesel engine dynamometer, in terms of engine torque, engine power, and brake specific fuel consumption. It was found that these biodiesel can be used as the alternative fuel based on the performance of engine dynamometer, where the results show nearly similar with regular diesel.